Effect of phentolamine mesylate on duration of soft tissue local anesthesia in children - Nosrat Nourbakhsh; Farzaneh Shirani; Mahdi Babaei (Wolters Kluwer Medknow Publications, 2012)
Objective: Addition of vasoconstrictors to local anesthesia results in prolonged pain control. However, associated soft-tissue anesthesia (STA) of the lips and tongue typically lasts 3-5 hours which is longer than required time for pain control after routine dental procedures can lead to inadvertent biting of the soft tissue, particularly in children. The present study aimed to evaluate phentolamine mesylate (PM) effect on duration of STA and incidence of soft-tissue trauma after mandibular block injection. Methods: This randomized, double-blinded, controlled clinical trial included 54 patients with the age of 4-11 years. In group 1 at the first visit, the children received ordinary local anesthetic (LA) consisting of lidocaine 2% and epinephrine 1:80,000 and the PM injection was performed 30 minutes later. At the second visit, the contralateral side received LA injection then the dental procedure was done and a sham injection was performed. In group 2 at the first visit, patients received control injection and at the second visit received PM injection. Then the reversal time for normal sensation of soft tissue, the vital signs, and the incidence of soft-tissue trauma in a period of 3-5 hours after injection were evaluated. Findings: There was a statistically significant difference (P < 0.001) in recovery time of normal lip sensation between case and control groups and also between two groups (P < 0.003). Incidence of soft-tissue trauma between case and control groups showed a statistically significant difference (P < 0.039). Conclusion: PM can be considered as a safe and effective drug for reduction of reversal time of STA after dental procedures.